2011
DOI: 10.1021/ja2060929
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of99Tc Pertechnetate by Nanometer-Sized Metal Oxides: New Strategies for Formation and Sequestration of Low-Valent Technetium

Abstract: ABSTRACTproduct. The reduction and incorporation of TcO 4 -was accomplished in a "one pot" reaction using both sunlight and UV irradiation, and monitored as a function of time using multinuclear NMR and radio TLC. The process was further probed by the "step-wise" generation of reduced α 2 -P 2 W 17 O 61 12-through bulk electrolysis followed by the addition of TcO 4 -. serving as models for metal oxides, POMs may also provide a suitable platform to study the molecular level dynamics and mechanisms of the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 72 publications
2
36
0
3
Order By: Relevance
“…This fundamental study, along with our previous reports using the α 2 ‐[P 2 W 17 O 61 ] 10– and Keggin ions for binding of Tc,, demonstrate that POMs have sites that can stabilize different Tc oxidation states and can be useful to understand the coordination chemistry of reduced Tc. Specifically, we demonstrated the different coordination geometries and sites provided by POMs dictate the Tc oxidation states (IV and V).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This fundamental study, along with our previous reports using the α 2 ‐[P 2 W 17 O 61 ] 10– and Keggin ions for binding of Tc,, demonstrate that POMs have sites that can stabilize different Tc oxidation states and can be useful to understand the coordination chemistry of reduced Tc. Specifically, we demonstrated the different coordination geometries and sites provided by POMs dictate the Tc oxidation states (IV and V).…”
Section: Discussionsupporting
confidence: 60%
“…The ITLC data of PW 12 : Tc A and SiW 12 : Tc A, from year 1, taken immediately after the bulk electrolysis reaction, correlates with the XANES and EXAFS data described above and supports the formation of a Tc V =O PW 11 species and a Tc IV species for the SiW 12 complex. In our previous work, we observed that when the reduced Tc is associated with the POM, for example, when the Tc V is incorporated into a defect site, such as in the α 2 P 2 W 17 , the activity is observed at or near the origin with significant tailing . We have also observed that radiolanthanides incorporated into the defect of α 2 P 2 W 17 exhibit similar ITLC data, where activity remains at the origin .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Esaterako, hondakin erreaktiboen desaktibaziorako erreminta baliagarri bezala ikertu dira askotan, teknezio, uranio edo neptunio katioiei lotzeko duten afinitate handia aprobetxatuz [11]. Hondakin-uren tratamenduari dagokionez, hainbeste industriatan erabiltzen diren koloratzaile eta pestiziden oxidazio heterogeneo katalitikoan sarri hartzen dute parte, baina baita konposatu kutsagarrien analisian ere.…”
Section: Gasen Harrapaketa Eta Hondakin-uren Tratamenduaunclassified
“…Ildo beretik jarraituz, kutsatzaileak desagerraraztea baino are garrantzitsuago da hauen erabilera ekiditea. Ildo honetan, kloroan oinarritutako konposatuen ordezko «berde» bezala aurkeztu da [AlVW 11 O 40 ] 6-POM anioia, papergintzan, zuritzearekin lotutako egurraren deslignifikazio prozesurako [13].…”
Section: Gasen Harrapaketa Eta Hondakin-uren Tratamenduaunclassified